Investigação do diagrama de fases do niobato de chumbo e bário através de espalhamento Raman - Silva, João José de Lima (2004)
In this work, we investigated the phase diagram of the tungsten-bronze ferroelectric PbxBa1¡xNb2O6(PBN). The main experimental technique was Raman scattering, which was used to measured the samples with x = 0:56, 0.60 and 0.70 as a function of the temperature between 10 and 750 K. However, the intrinsic complexity of the Raman spectra of the PBN motivated us to perform a careful analysis of the data treatment methods. In order to verify the e±ciency of the proposed methodology, we applied it to the study of a ferroelectric belonging to the Aurivillius family, the Bi 1:75 Te0:25 SrNb1:75Hf0:25O9. Our results in the PBN samples allow us to verify that no structural phase transitions are exhibited by them at low temperatures. On the other hand, above room temperature we observed the ferro-paraelectric phase transition in all samples at the temperatures predicted by the phase diagram. Based on these results, the PBN phase diagram was re-discussed showing that the extension of the morphotropic phase boundary at low temperatures does not agree with prediction of the literature. As a consequence, a modification of this phase diagram was proposed.